Brown's boundary control and legal principles - Robillard, Walter G. (Walter George), 1930-; Wilson, Donald A., 1941-; Brown, Curtis M. (Curtis Maitland), 1908-1993. (Hoboken, New Jersey : Wiley, 2013)
The new edition of Brown's Boundary Control and Legal Principles has been updated to reflect ongoing changes in surveying technology and surveying law, notably by adding water boundary expert George Cole as a contributor to revamp information on Riparian and Littorial Boundaries. Additionally, a new appendix has been introduced containing a comprehensive list of surveying books that have been referenced in court cases and legal decisions as persuasive authority over the years. It is indispensable reading for students and practicing studying for the Fundamentals of Land Surveying licensure exam.
History and concept of boundaries -- How boundaries are created -- Ownership, transfer, and description of real property & accompanying rights -- Boundaries, law, and related presumptions -- Creation and interpretation of metes and bounds and other non-sectionalized descriptions -- Creation and retracement of glo boundaries -- Federal and state non- sectionalized land surveys -- Locating easements and reversions -- Riparian and littoral boundaries -- Retracing and ?resurveying? sectionalized lands -- Locating sequential conveyances -- Locating simultaneously created boundaries -- Locating combination descriptions and conveyances -- Role of the surveyor -- The ethics and moral responsibilities of boundary creation and of retracements.
Includes index.
Includes bibliographical references.
Description based on print version record and CIP data provided by publisher.
Keywords: Boundaries (Estates) -- United States; Surveying -- Law and legislation -- United States; Title examinations -- United States; LAW -- Administrative Law & Regulatory Practice; Boundaries (Estates); Surveying -- Law and legislation; Title examinations; United States; Electronic books; Electronic books